2011
DOI: 10.1038/nature10621
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an oxygen-depleted liquid outer core of the Earth

Abstract: On the basis of geophysical observations, cosmochemical constraints, and high-pressure experimental data, the Earth's liquid outer core consists of mainly liquid iron alloyed with about ten per cent (by weight) of light elements. Although the concentrations of the light elements are small, they nevertheless affect the Earth's core: its rate of cooling, the growth of the inner core, the dynamics of core convection, and the evolution of the geodynamo. Several light elements-including sulphur, oxygen, silicon, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
91
0
1

Year Published

2012
2012
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 27 publications
5
91
0
1
Order By: Relevance
“…Comparison between V P − ρ of hcp-Fe and Earth's core indicates significant V P − ρ differences that call for the addition of approximately 8-10 wt % light elements in the outer core and 4 wt % in the inner core (e.g., [12][13][14][15]23) (Fig. 3B) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison between V P − ρ of hcp-Fe and Earth's core indicates significant V P − ρ differences that call for the addition of approximately 8-10 wt % light elements in the outer core and 4 wt % in the inner core (e.g., [12][13][14][15]23) (Fig. 3B) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Deciphering these observations requires solid knowledge about the composition of the Earth's inner core and, therefore, the elasticity of candidate Fe alloys (7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Since F. Birch pointed out in the 1950s that Earth's core is too dense if composed of Fe or Fe-Ni alloy alone (13), a number of candidate major light elements, including oxygen (O), silicon (Si), sulfur (S), carbon (C), and hydrogen (H), have been suggested via cosmochemical, geochemical, and geophysical evidence (17).…”
mentioning
confidence: 99%
“…Ideal mixing has been the standard working hypothesis in this kind of study (6,19,22) and will need to be verified by future work. However, our study reinforces this hypothesis by showing that (i) the binary systems are perfectly ideal (as can be seen by the perfectly linear fits of density versus concentration) and (ii) our calculations were compared with existing shockwave data (19,(22)(23)(24) on molten Fe, Fe-O, and Fe-S alloys and found them to be in excellent agreement (SI Appendix, section 3).…”
mentioning
confidence: 99%
“…Ideal mixing has been the standard working hypothesis in this kind of study (6,19,22) and will need to be verified by future work. However, our study reinforces this hypothesis by showing that (i) the binary systems are perfectly ideal (as can be seen by the perfectly linear fits of density versus concentration) and (ii) our calculations were compared with existing shockwave data (19,(22)(23)(24) on molten Fe, Fe-O, and Fe-S alloys and found them to be in excellent agreement (SI Appendix, section 3). It should also be noted that high-pressure experiments have shown that miscibility gaps vanish at high pressures (25)(26)(27)(28), hence also indicating that high-density liquids tend to have a simpler thermodynamic behavior than their low-pressure counterpart.…”
mentioning
confidence: 99%
See 1 more Smart Citation